Application of the 4-Element Movement System Model to Sports Physical Therapy Practice and Education - Ryan Zarzycki; Philip Malloy; Brian J Eckenrode; Jane Fagan; Molly Malloy; Kathleen K Mangione (International Journal of Sports Physical Therapy)
The 4-Element Movement System Model describes primary elements (motion, force, motor control, and energy) essential to the performance of all movements. The model provides a framework or scaffolding which allows for consistent processes to be used in examination and intervention decisions. The process starts with task identification followed by a systematic observation of control, amount, speed, symmetry, and symptoms during movement. Testable hypotheses are generated from the observations which inform the examination and the interventions. This commentary describes the use of the 4-Element Movement System Model in entry level and post-graduate residency educational programs and in clinical care with three common sports-related diagnoses.